Pedagogical Knowledge of English Teachers on Speech Acts in Senior High School Level of West Nusa Tenggara - kamarudin kamarudin (The Center for Language Development, Mataram State Islamic University., 2019)
As an English teacher, communicating through English language properly and thoroughly is highly required particularly at Senior High School level. They are expected to communicate politely since teachers are the role model of teaching. As a professional teacher, English teachers must have professional competencies such as speech acts proficiencies. Speech act is included into spoken English and is taught in Senior High School level in order to develop students’ communicative competence. This is a descriptive qualitative research and is aiming at describing pedagogical knowledge of English teachers on speech acts in Senior High School level of West Nusa Tenggara. The knowledge itself is divided into some branches, they are the ability to define speech acts, ability to identify speech acts conversation and ability to identify speech act utterances. The researcher conducted the interview to collect the data. The data are obtained from the interview and the tape recorder to record the interview process. After analyzing the data, the researcher found that Senior High School teachers mostly can answer questions about speech acts. They can define speech acts, they can identify the speech act conversations and they can identify the speech act utterances. In conclusion, the knowledge of speech acts of Senior High School teachers is categorized very good because they can answer most questions correctly. Therefore, Senior High School teachers fulfill professional language competencies; they comprehend teaching materials and have good pedagogical skills.